Amino Acid Degrading Enzymes and Autophagy in Cancer Therapy - Wang, Ziyu; Xie, Qinghong; Zhou, Haifeng; Zhang, Min; Shen, Jie; Ju, Dianwen (Frontiers in Pharmacology, 2021)
Recently, there has been renewed interest in metabolic therapy for cancer, particularly in amino acid deprivation by enzymes. L-asparaginase was approved for the treatment of acute lymphoblastic leukemia by U.S. Food and Drug Administration. Arginine deiminase and recombinant human arginase are developed into clinical trials as potential cancer therapeutic agents for the treatment of arginine-auxotrophic tumors. Moreover, there are other novel amino acid degrading enzymes, such as glutaminase, methionase, lysine oxidase, phenylalanine ammonia lyase, developed for the treatment of malignant cancers. One of the greatest obstacles faced by anticancer drugs is the development of drug resistance, which is reported to be associated with autophagy. Autophagy is an evolutionarily conserved catabolic process that is responsible for the degradation of dysfunctional proteins and organelles. There is a growing body of literature revealing that autophagy, in response to metabolism stress, could be induced by amino acid deprivation. Nowadays, manipulating autophagy in combination with amino acid degrading enzymes as a potential therapeutic approach is actively being investigated in preclinical studies. Importantly, shedding light on how autophagy fuels tumorous metabolism during amino acid deprivation will enable more potential combinational therapeutic strategies. Here, we summarize the recent advances of several potential anticancer enzymes and highlight the promising combinational therapeutic strategy of amino acid degrading enzymes and autophagy modulators in tumors.